Synthesis and structure of macrocyclic dinickel(II) complex with 5-(4-pyridyl)tetrazolate as coligand - Voitekhovich, Sergei V.; Kersting, Berthold; Ivashkevich, Oleg A. (Journal of the Belarusian State University. Chemistry, 2021)
The dinuclear nickel(II) complex [Ni2LmClO4] + , where Lm represents a 24-membered macrocyclic hexaaza-dithiophenolate ligand, reacts with 5-(4-pyridyl)tetrazole (PyrCN4H) to give the dinuclear complex [Ni2Lm(PyrCN4)]+ . The new complex was both isolated as perchlorate or tetraphenylborate salts and characterised by elemental analysis and IR spectroscopy. The structure of [Ni2Lm(PyrCN4)]BPh4 ⋅ MeCN was determined by single crystal X-ray diffraction, showing that tetrazolate units are in a N2,N3-bridging mode to generate dioctahedral N3Ni(µ-S)2(µ-N4CPyr)NiN3 core.
Keywords: macrocyclic ligands; nickel complexes; tetrazolates; X-ray diffraction analysis